2020
DOI: 10.1093/gigascience/giz159
|View full text |Cite
|
Sign up to set email alerts
|

A genome alignment of 120 mammals highlights ultraconserved element variability and placenta-associated enhancers

Abstract: Background Multiple alignments of mammalian genomes have been the basis of many comparative genomic studies aiming at annotating genes, detecting regions under evolutionary constraint, and studying genome evolution. A key factor that affects the power of comparative analyses is the number of species included in a genome alignment. Results To utilize the increased number of sequenced genomes and to provide an accessible resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 87 publications
2
36
0
Order By: Relevance
“…Genes showing evidence of positive selection were subsequently explored using protein structure prediction and modelling methods ( Supplementary Data 3). To systematically screen for gene losses, we used a previously developed approach 53 (Supplementary Note 4.5), and required that less than 80% of the ORF was intact in all six bats, excluding genes classified as lost in more than 20% of non-Chiroptera Laurasiatherian mammals contained in our 120-mammal multiple genome alignment 88 (Supplementary Note 4.5). We confirmed the presence of inactivating mutations in independently sequenced bat species.…”
Section: Gene Selection Loss and Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes showing evidence of positive selection were subsequently explored using protein structure prediction and modelling methods ( Supplementary Data 3). To systematically screen for gene losses, we used a previously developed approach 53 (Supplementary Note 4.5), and required that less than 80% of the ORF was intact in all six bats, excluding genes classified as lost in more than 20% of non-Chiroptera Laurasiatherian mammals contained in our 120-mammal multiple genome alignment 88 (Supplementary Note 4.5). We confirmed the presence of inactivating mutations in independently sequenced bat species.…”
Section: Gene Selection Loss and Gainmentioning
confidence: 99%
“…4 5 6 7 8 9 10 12 14 16 18 20 22 24 26 28Presence of 197 non-exonic ultraconserved elements Miniopterus (Eckalbar et al 2016) 3 20 align at ≥ 85% identity to the human sequence. UCEs are highly conserved among mammals 88 and are expected to be present in complete assemblies. Bar charts show the number of detected UCEs that align at these stringent parameters.…”
Section: Evolution Of Noncoding Genomic Regionsmentioning
confidence: 99%
“…We applied a previously developed approach (Sharma, et al 2018a) to screen for geneinactivating mutations in TLR5 using a genome alignment of 120 placental mammals ( Supplementary Table 1) (Hecker, et al 2020). This screen revealed that the single coding exon of TLR5 exhibits stop codon mutations, smaller frameshifting insertions or deletions, or larger deletions in the genome assemblies of 17 species belonging to 14 distinct lineages (gorilla, orangutan, guinea pig, rabbit, pig, alpaca, Yangtze river dolphin, bighorn sheep, Weddell seal, Hawaiian monk seal, walrus, Malayan and Chinese pangolins, little brown bat, elephant, armadillo).…”
Section: Resultsmentioning
confidence: 99%
“…Since the two TLR5 transcripts in human GENCODE version 32 (Harrow, et al 2012) annotate an identical single coding exon and only differ in 5' UTR exons, we focused on this single coding exon. We used human as the reference species and initially considered a total of 119 non-human mammals that are part of a 120-mammal genome alignment (Hecker, et al 2020). The TLR5 sequence provided by this alignment was re-aligned with CESAR (Codon Exon Structure Aware Realigner) (Sharma, et al 2016;) to avoid spurious frameshifts due to alignment ambiguities.…”
Section: Investigating and Validating Losses Of Tlr5mentioning
confidence: 99%
“…little brown bat and other hibernating bats and mouse lemur or enter seasonal torpor e.g., cape golden mole and tree shrew. Our statistical analysis using phylogenetic logistic regression(65) considering phylogeny of the 113 species from nine mammalian orders(66) shows phylogeny-independent significant correlation (R 2 0.77, p-value = 2.72e-06, alpha 0.00011) between the presence of the glutamine (Gln, Q) variant and cold adaptation, hibernation or ability to enter torpor…”
mentioning
confidence: 99%